Analysis of Pragmatic Elements in the Children’s book The Very Hungry Caterpillar - Komang Trisnadewi (English Education Study Program Faculty of Teacher Training and Education, 2025)
This study conducts a review to analyze the pragmatic elements in Eric Carle’s The Very Hungry Caterpillar, focusing on how these elements contribute to the book's effectiveness as a tool for engaging young readers and enhancing language learning. The study addresses two main questions: (1) how pragmatic features such as speech acts, implicature, deixis, and conversational maxims are used in the book to convey meaning and facilitate interaction, and (2) the implications of these pragmatic elements for teaching English to children. This qualitative study employs content analysis to examine the book's text and illustrations through a pragmatic lens. The review identifies that The Very Hungry Caterpillar employs declarative and imperative speech acts to invite reader participation and enhance engagement. Implicature is used to convey implicit meanings related to the caterpillar’s growth and transformation, supported by contextual cues and illustrations. The study highlights that these pragmatic elements can influence educational strategies. Interactive reading sessions, activities focusing on deictic expressions, and exercises that encourage inference and adherence to conversational maxims are recommended as practical applications. These methods support early literacy development and promote meaningful language use, providing effective tools for educators to enhance language acquisition and communication skills in young learners. By integrating findings from existing research on pragmatics and children's literature, this study offers new insights into the role of pragmatic elements in early childhood education. The practical applications derived from the book’s use of language features underscore its value as an educational tool, contributing to improved teaching practices and language learning outcomes for young children.